Effect of infertile semen samples on mRNA-based body fluid identification by KLK3 and PRM1. Issue 1 (December 2019) - Zhao, Huan; Tian, Huan; Bai, Peng; Li, Zhilong; Peng, Duo; Chen, Dan; Feng, Tao; Jiang, Haoyan; Li, Xinyao; Liang, Weibo; Li, Fuping
Abstract: In the past decades, mRNA marker has been well demonstrated the remarkable progress and wide application for its high sensitivity, specificity and robustness. However, according to previous studies, infertility has become a global health problem. Therefore given the increasing occurrence of male infertility, forensic researchers have to consider the impact of semen infertility on semen identification. In present study, normal semen (NS) asthenospermia (AS) and oligospermia (OS) semen samples were collected. The expression of semen-specific mRNA markers (KLK3, PRM1) was detected using end-point PCR. The results showed that KLK3 was almost not influenced by infertile semen samples. In contrast, PRM1 couldn't be detected in all the infertile semen samples, indicating that it may not be ideal mRNA marker to identify semen samples. The present study aimed to explore the effect of the infertile semen on body fluid identification and to identify semen-specific mRNAs.